ANALYSIS OF CURRENT MECHANISMS FOR ATTRACTING FOREIGN INVESTMENTS TO THE ECONOMY (Marketing Journal, 2025)
The article analyzes the existing mechanisms for attracting foreign investments into Uzbekistanʼs economy. In recent years, a number of reforms have been implemented in the country to create favorable conditions for foreign investors, improve legislation, simplify the taxation system, and develop free economic zones. The study identifies positive and negative factors affecting the investment climate and evaluates the effectiveness of current mechanisms. It also examines the entry of foreign investors into t he Uzbek market, the opportunities provided to them, the bureaucratic obstacles encountered, and ways to overcome them. In conclusion, proposals and recommendations for improving investment policy were developed.
Keywords: foreign investment; investment climate; economic reforms; investors; legal guarantees; investment attractiveness; mechanism; reform effectiveness